BİR AĞIT OLARAK İNSAN - Ahmet İnam (Felsefe Dünyası)
Human Being as an ethical being can be represented as an elegy. She creates herself by poeticizing her life. She endeavours to live her life like a poem. But her life is nothing but an elegy. Why is it so? In this paper a philosophical explication of the concept of "elegy" will be explicated and and onto-ethical implication of it will be descri